Towards a natural classification of Dothideomycetes 2: The genera Cucurbidothis, Heterosphaeriopsis, Hyalosphaera, Navicella and Pleiostomellina (Dothideomycetes incertae sedis) - Ariyawansa, Hiran A.; Thambugala, Kasun M.; Kang, Ji-Chuan; Alias, Siti A.; Chukeatirote, Ekachai; Hyde, Kevin D. (Phytotaxa, 2014)
By re-examining the generic types of Dothideomycetes genera, incertae sedis we can propose higher level positions according to the morphology based on modern taxonomic concepts but, more importantly, we illustrate the taxa so that they are better understood. In this way the taxa can be recollected and molecular data can be used to place them in a natural taxonomic framework of the Ascomycota. The generic types of Cucurbidothis, Heterosphaeriopsis, Hyalosphaera, Navicella and Pleiostomellina were re-examined in this study. A synopsis of the history and descriptions and illustrations of these genera are provided. Cucurbidothis is placed in Cucurbitariaceae as a distinct genus, while Navicella and Pleiostomellina are referred to Melanommataceae and Parmulariaceae respectively based on the morphological similarities. Heterosphaeriopsis and Hyalosphaera are retained in Dothideomycetes genera incertae sedis as they are not typical of any existing families of Dothideomycetes. Fresh collections of these genera are needed for further studies, so that they can be epitypified and molecular data can be analyzed to stabilize their natural classification.